(untitled) (Revista de História da UEG (REVHIST), 2024)
Before the emblematic institutions of indigenism and anthropology were consolidated, various projects linked to the study of the indigenous population and the generation of public policies were carried out in Mexico. This is the case of the University Mission in the Mezquital Valley (1936), a project undertaken by the National University that did not have the support of the federal government, as it was considered contrary to the socialist ideology of Cardenismo, that is, liberal, was temporarily linked to the federal agency in charge of coordinating policies on indigenous matters, the Department of Indigenous Affairs. This paper allows us to observe one of the spaces that we have not recognized within the anthropological and indigenous feat, broadening the view to other fields of knowledge and institutions, as well as part of the political and ideological tensions that mediated the success and failure of such projects. Keywords: University Mission; Mezquital Valley; Department of Indigenous Affairs; Indigenism; History of Anthropology.